Electronic information educational environment as an ecosystem in the pedagogical process of a modern university - Bolshakova, Alina Sergeevna; Mokhnatkina, Ksenia Vladimirovna (Razvitie obrazovaniâ (Online), 2024)
Development of the EIEE (electronic information and educational environment) is one of the most important topics in modern pedagogical research. This process is currently undergoing a lot of changes and requires its detailed understanding within the framework of pedagogical science, as modern educational programmes for specialists’ training require implementation of innovative digital technologies. Therefore, the purpose of the study is to carry out theoretical analysis and case study in order to systematize this concept in the context of implementing educational programs for training highly qualified specialists in various sectors of the digital economy. EIEE plays the key role in terms of implementing educational programs for training highly qualified specialists in various areas of digital economy. This paper provides generalized analysis of existing theoretical approaches to the concept of "ecosystem" and considers various views on EIEE’s development. Particular attention is paid to the authors’ approach, which is based on cooperation with industrial partners. In this context, it is proposed to create EIEE through the development of technical specifications, integration of cross-platform solutions and sharing resources. In the course of the study, the author comes to the conclusion that EIEE’s development is an important step towards evolution of educational programmes that meet the requirements of modern digital economy and contribute to training of a new generation of specialists, who are ready for challenges that future presents.